Covid-19 Pandemic Reviewed in Constitutional Law Perspective - Ainuddin Ainuddin (Jurnal IUS Kajian Hukum dan Keadilan, 2021)
Many countries are unsure to decide on legal instruments to use to overcome the crisis caused by the Covid-19 pandemic. Some chose to establish a state of emergency based on the constitution, while others used the applicable law regarding disasters or health crises, implemented new legislation, and issued another community restriction enforcement policy namely PPKM. The stipulation of a state of emergency allows the state to deviate from the rule of law. Therefore, the determination of the emergency status is potentially be misused. The method of this research is normative legal research using statute and conceptual approaches. The result of this research experienced that the Indonesian government chose to use Health Emergency in Law 6 of 2018 and Non-Natural Disaster Emergency in Law 24 of 2007 to deal with the Covid-19 Pandemic regardless of Article 12 of the 1945 Constitution providing provisions for a constitutional emergency. The emergency status does not entirely involve Article 12 of the 1945 Constitution as the basis for its formation. Thus, the term emergency is not a state of emergency as referred to in the study of emergency constitutional law (only de facto not de jure). Although there are restrictions, this certainly does not apply to basic rights, especially to non-derogable rights groups.